2018
DOI: 10.2139/ssrn.3191954
|View full text |Cite
|
Sign up to set email alerts
|

Trusting Nudges? Lessons from an International Survey

Abstract: In the past decade, policymakers have increasingly used behaviourally informed policies, including 'nudges,' to produce desirable social outcomes. But do people actually endorse those policies? This study reports on nationally representative surveys in five countries (Belgium, Denmark, Germany, South Korea, and the US) carried out in 2017/2018. We investigate whether people in these countries approve of a list of 15 nudges regarding health, the environment, and safety issues. A particular focus is whether trus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
26
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(30 citation statements)
references
References 11 publications
2
26
0
Order By: Relevance
“…Research shows a higher percentage of women than men support nudges, including defaults (Diepeveen et al, 2013;Loibl et al, 2018;Reisch and Sunstein, 2016). In addition, other studies (Jung and Mellers, 2016;Sunstein et al, 2018) found empathy is associated with higher levels of support for nudges (e.g. organ donation, healthier eating habits).…”
Section: Gendermentioning
confidence: 95%
“…Research shows a higher percentage of women than men support nudges, including defaults (Diepeveen et al, 2013;Loibl et al, 2018;Reisch and Sunstein, 2016). In addition, other studies (Jung and Mellers, 2016;Sunstein et al, 2018) found empathy is associated with higher levels of support for nudges (e.g. organ donation, healthier eating habits).…”
Section: Gendermentioning
confidence: 95%
“…However, recent studies have shown that policy makers can be transparent about nudges without decreasing their effectiveness (Bruns et al ). Furthermore, another option would be to measure attitudes toward the social norm intervention among a group of GPs and patients who were not part of the study (see, e.g., Sunstein, Reisch, and Kaiser ). This could indicate the extent to which GPs and patients would endorse such a behavior change intervention.…”
Section: A Conceptual Framework For Behavior Change By Governmentsmentioning
confidence: 99%
“…In this vein, the research could be adapted to Japan, China, or other Eastern countries to fill out understanding of primary differences from the West. Sunstein et al (2019) further analyzed the nudge preferences from the 15 question survey of SRR (2018) with mediating variables related to institutional trust-including a sample from Korea-that provides a model for examining why people approve of nudge policies related to environmental protection and health. This kind of work could be expanded to other nudge issues as well as exploring the effects of more mediating variables of demographic and socio-cultural dimensions.…”
Section: Resultsmentioning
confidence: 99%
“…While this study was initiated before the publication of SRR (2018), it is most certainly an extension of that study as well as being based on the same survey featured at various extents in works by Sunstein (2015Sunstein ( , 2016aSunstein ( , 2016b, and Sunstein et al (2019). It follows most closely on the approach and format of SRR, addressing their concern that, "relatively little work has been conducted to determine whether citizens approve of [nudges]" (2018: 3) and contributing a replication and micro-level analysis of their survey in Korea.…”
Section: H2: Koreans Are More Favorable To System 2 Directed Nudgesmentioning
confidence: 99%
See 1 more Smart Citation